2009
DOI: 10.1111/j.1748-1716.2008.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistin increases islet blood flow and decreases subcutaneous adipose tissue blood flow in anaesthetized rats

Abstract: Acute administration of resistin markedly affects the blood perfusion of both the pancreas and subcutaneous white adipose tissue depots. At present it is unknown whether resistin exerts a direct effect on the vasculature, or works through local or systemic activation of endothelial cells and/or macrophages. The extent to which this might contribute to the insulin resistance caused by resistin is yet unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…In studies of fixed human pancreata, resistin was shown to be expressed in human beta cells, but not alpha cells, and its expression increased with T2D (AlSalam et al 2011). Finally, another potential mechanism by which resistin may impact on beta cell function is by enhancing blood flow to the pancreas (Danielsson et al 2009). Beta cell function is negatively impacted by hypoxia (Cantley et al , 2013 and hypoxia-inducible factor 1a activation (Cantley et al 2009); therefore, as nutrient stimulation can lead to a transient decrease in oxygen tension (Bensellam et al 2012), resistin may help to sustain adequate islet perfusion and oxygenation during times of high-metabolic demand.…”
Section: Resistinmentioning
confidence: 98%
“…In studies of fixed human pancreata, resistin was shown to be expressed in human beta cells, but not alpha cells, and its expression increased with T2D (AlSalam et al 2011). Finally, another potential mechanism by which resistin may impact on beta cell function is by enhancing blood flow to the pancreas (Danielsson et al 2009). Beta cell function is negatively impacted by hypoxia (Cantley et al , 2013 and hypoxia-inducible factor 1a activation (Cantley et al 2009); therefore, as nutrient stimulation can lead to a transient decrease in oxygen tension (Bensellam et al 2012), resistin may help to sustain adequate islet perfusion and oxygenation during times of high-metabolic demand.…”
Section: Resistinmentioning
confidence: 98%
“…Auch Resistin wird von Fettzellen proportional zur Fettmasse synthetisiert. Bei Normalgewichtigen führt es zu einem vermehrten Blutfluss zum Pankreas, bei adipösen Patienten fördert es jedoch die Insulinresistenz und Glukoseintoleranz (15,16). Von Hepatozyten wird das o.g.…”
Section: Nafld Und Adipositasunclassified
“…An ability to reduce expression levels of insulin receptor in pancreatic beta-cells has been reported, 28 as has a role in islet blood flow. 29 As resistin is expressed in pancreatic beta-cells, it remains to be shown whether these effects are due to locally secreted resistin or an endocrine effect of the fat-secreted form.…”
Section: Adipokines and Glucose Homeostasis – Regulation Of Insulin Smentioning
confidence: 99%